Giant mesenteric cyst of gastric origin: a case report with imaging findings - Ayaz, Ümit Yaşar; Dilli, Alper; Api, Arman (The Turkish Journal of Pediatrics, 2011)
We present a very rare case of a giant gastric mesenteric cyst with ultrasonography (US) and computed tomography (CT) findings. An eight-year-old boy was referred for treatment of an intraabdominal cyst, known to exist for six years. On abdominal US, a giant, thin-walled, unilocular intraabdominal cyst was demonstrated, extending from the epigastric region to the pelvis and measuring 18 x 15 x 6 cm. In contrast-enhanced abdominal CT, the cyst was demonstrated as a giant, unilocular, hypodense, non-enhancing structure, located dominantly on the right side of the abdomen. During open surgery, the cyst was found to originate from the mesentery-serosa of the gastric antrum and was filled with serous fluid. The cyst was excised totally. Both surgery and pathology confirmed the diagnosis of mesenteric cyst, originating from the stomach. The patient was discharged in good health. US and CT were effective in defining the features of the giant gastric mesenteric cyst and in narrowing the differential diagnosis in favor of mesenteric cyst.